Pro Sql Azure - Klein, Scott; Roggero, Herve; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
SQL Azure represents Microsoft$1 (Bs cloud-based delivery of its enterprise-caliber, SQL Server database management system (formerly under the code name "Oslo"). Pro SQL Azure introduces you to this new platform, showing you how to program and administer it in a variety of cloud computing scenarios. You$1 (Bll learn to program SQL Azure from Silverlight, ASP.NET, WinForms, and from SQL Reporting Services. You$1 (Bll also understand how to manage the platform by planning for scalability, troubleshooting performance issues, and implementing strong security. Shows how to use SQL Azure from Silverlight, ASP.NET, and more Covers management, scalability, and troubleshooting Addresses the all-important issue of securing your datas
Getting Started with SQL Azure -- Design Considerations -- Setting Up and Configuring -- Security -- Data Migration and Backup Strategies -- Programming with SQL Azure -- OData with SQL Azure -- Reporting Services with SQL Azure -- Windows Azure and ASP.NET -- Designing for High Performance -- SQL Azure Data Sync Services -- Performance Tuning.
Keywords: Computer science; Database management; Computer Science; Computer Science, general; Database Management